The shadow world inside the global arms trade - Feinstein, Andrew 1964- (Penguin Books, 2012)
Reveals the corruption behind BAE's controversial transactions in South Africa, Tanzania and eastern Europe and the relationships that characterise the US Congressional-Military-Industrial Complex. This title exposes both the formal government-backed trade in arms as well as the illicit deals and lays bare the shocking links between the two.